(untitled) (Research, Society and Development, 2020)
The cultivation of soybeans is of global socioeconomic importance, therefore, studies are needed to increase its productive performance. Thus, this study aimed to evaluate the effect of agronomic traits due to the application of nitrogen sources and rates associated with inoculation with Bradyrhizobium japonicum on the protein content and grain yield of soybean. A randomized block design was used, in a 2 × 2 × 5 factorial scheme: two locations (UFMS 1 and UFMS 2), two sources of nitrogen fertilizer [urea (45% N) and ammonium sulfate(21% N)] and five nitrogen rates (0, 50, 100, 150 and 200 kg ha–1), with four replications. At the R3 stage, plant height, leaf chlorophyll content, leaf area and shoot dry matter were evaluated. At stage R8, first pod height, pods number per plant, grain number per pod, mass of thousand grains, grain yield and crude protein content were measured. The results show that in the experiment conducted in the UFMS 1 area, the leaf area and the mass of thousand grains were the agronomic traits that have the greatest positive direct effect on grain yield and protein content, respectively. In the UFMS 2 area, the mass of a thousand grains and the total dry mass were the agronomic traits that have the greatest direct positive effect on grain yield and protein content, respectively.